Association of chronic kidney disease with acute clinical outcomes and hospitalization costs of cancer resection - Sara Sakowitz; Syed Shahyan Bakhtiyar; Saad Mallick; Amulya Vadlakonda; Ifigenia Oxyzolou; Konmal Ali; Nikhil Chervu; Peyman Benharash (PLoS ONE, 2025)
Purpose Patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD) have been noted to face increased cancer incidence. Yet, the impact of concomitant renal dysfunction on acute outcomes following elective surgery for cancer remains to be elucidated. Methods All adult hospitalizations entailing elective resection for lung, esophageal, gastric, pancreatic, hepatic, or colon cancer were identified in the 2016–2020 National Inpatient Sample. Based on stage of renal dysfunction, CKD patients were sub-classified as CKD1-3, CKD4-5, or ESRD (others: Non-CKD). Multivariable regression models were developed to assess the association of comorbid CKD/ESRD with in-hospital mortality, perioperative complications, and resource utilization. Results Of ~515,145 patients, 32,195 (6.2%) had CKD (5.1% CKD1-3, 0.7% CKD4-5, 0.5% ESRD). The incidence of CKD among patients undergoing cancer resection increased from 5.3% in 2016 to 7.3% in 2020 (P<0.001). Following risk adjustment, CKD1-3 and CKD4-5 remained linked with similar likelihood of mortality and hospitalization costs, but greater need for blood transfusion (CKD1-3 AOR 1.21, CI 1.09–1.35; CKD4-5 AOR 1.73 CI 1.38–2.18). CKD4-5 was also associated with greater odds of infection (AOR 1.88, CI 1.34–2.62) and respiratory sequelae (AOR 1.36, CI 1.05–1.77). Further, ESRD was linked with greater odds of in-hospital mortality (AOR 2.74, CI 1.69–4.45), infection (AOR 2.31, CI 1.62–3.30) and respiratory complications (AOR 1.72, CI 1.31–2.26), as well as greater resource utilization, relative to Non-CKD. Conclusion Comorbid renal dysfunction was linked with inferior clinical and financial outcomes following elective cancer resection. Future work is needed to develop optimal management strategies and recovery pathways for this complex cohort.